Economic Analysis in the Age of Artificial Intelligence: Enhancing Forecast Accuracy and Model Reliability - Frouté , Philippe; Madani , Kurosh; Meier , Olivier (International Transitions, 2025)
This article explores the impact of artificial intelligence (AI) on economic analysis, revisiting Lucas's critique through the lens of recent technological advancements. It highlights the contributions of machine learning-based models and bio-inspired approaches, while also addressing the limitations of current tools in terms of interpretability and applicability. By combining big data with innovative methods, AI helps to overcome traditional constraints, although it requires critical oversight to ensure the production of accurate and ethical economic forecasts.